Land-Use System and Forest Floor Explain Prokaryotic Metacommunity Structuring and Spatial Turnover in Amazonian Forest-to-Pasture Conversion Areas - Rocha, Fernando Igne; Ribeiro, Thiago Goncalves; Fontes, Marcelo Antoniol; Schwab, Stefan; Rodrigues Coelho, Marcia Reed; Lumbreras, Jose Francisco; Ferreira da Motta, Paulo Emilio; Teixeira, Wenceslau Geraldes; Cole, James; Borsanelli, Ana Carolina; Dutra, Iveraldo dos Santos [UNESP]; Howe, Adina; et al. (Frontiers Media Sa, 2021)
Advancing extensive cattle production is a major threat to biodiversity conservation in Amazonia. The dominant vegetation cover has a drastic impact on soil microbial communities, affecting their composition, structure, and ecological services. Herein, we explored relationships between land-use, soil types, and forest floor compartments on the prokaryotic metacommunity structuring in Western Amazonia. Soil samples were taken in sites under high anthropogenic pressure and distributed along a +/- 800 km gradient. Additionally, the litter and a root layer, characteristic of the forest environment, were sampled. DNA was extracted, and metacommunity composition and structure were assessed through 16S rRNA gene sequencing. Prokaryotic metacommunities in the bulk soil were strongly affected by pH, base and aluminum saturation, Ca + Mg concentration, the sum of bases, and silt percentage, due to land-use management and natural differences among the soil types. Higher alpha, beta, and gamma diversities were observed in sites with higher soil pH and fertility, such as pasture soils or fertile soils of the state of Acre. When taking litter and root layer communities into account, the beta diversity was significantly higher in the forest floor than in pasture bulk soil for all study regions. Our results show that the forest floor's prokaryotic metacommunity performs a spatial turnover hitherto underestimated to the regional scale of diversity.
Keywords: Amazonia; tropical rainforest; 16S rRNA gene; next generation sequencing; microbial biodiversity; land-use change; prokaryotes